2008
DOI: 10.1111/j.1432-2277.2007.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of transplantation versus resection for the treatment of small hepatocellular carcinoma

Abstract: Summary The best therapy for hepatocellular carcinoma (HCC) is still debated. Hepatic resection (HR) is the treatment of choice for single HCC in Child A patients, whereas liver transplantation (LT) is usually reserved for Child B and C patients with single or multiple nodules. The aim of this study was to compare HR and LT for HCC within the Milan criteria on an intention‐to‐treat basis. Forty‐eight patients were treated by LT and 38 by HR. The median time on the waiting list for transplantation was 118 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 41 publications
(49 reference statements)
1
33
0
Order By: Relevance
“…Due to the shortage of organ donor and the risk of disease progress on the waiting list, resection was suggested as the first-line treatment to the patients with small HCC and preserved liver function, and could achieve the favorable 5-year OS rate. The 5-year OS rate of resected HCC meeting Milan Criteria, according to the recent reports, ranged from 27% to 80% (Baccarani et al, 2008;Ueno et al, 2009;Lim et al, 2012), even 10-year OS rate in some centers could reach to 56% , and the 5-year RFS rate ranged from 21% to 57% (Ochiai et al, 2004;Lee et al, 2010;Lim et al, 2012). In our study, we observed that the 1-, 3-and 5-year OS rate were 96%, 81% and 76% respectively, and the 1-, 3-and 5-year RFS rate were 68%, 51% and 39% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the shortage of organ donor and the risk of disease progress on the waiting list, resection was suggested as the first-line treatment to the patients with small HCC and preserved liver function, and could achieve the favorable 5-year OS rate. The 5-year OS rate of resected HCC meeting Milan Criteria, according to the recent reports, ranged from 27% to 80% (Baccarani et al, 2008;Ueno et al, 2009;Lim et al, 2012), even 10-year OS rate in some centers could reach to 56% , and the 5-year RFS rate ranged from 21% to 57% (Ochiai et al, 2004;Lee et al, 2010;Lim et al, 2012). In our study, we observed that the 1-, 3-and 5-year OS rate were 96%, 81% and 76% respectively, and the 1-, 3-and 5-year RFS rate were 68%, 51% and 39% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Two tumors remained stable; the rest had 10-50% regression, which was sustained on follow-up imaging. The median follow up was 14 months (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Local tumor control was achieved in all treated tumors.Two patients were delisted as a result of cancer progression outside the treated field (one in the context of systemic metastases; yet another with progression of other untreated HCC in the liver).…”
Section: Discussionmentioning
confidence: 99%
“…Liver transplantation (LT) and resection remain the only options for cure.Out of the total patients with HCC on the waiting list, 20-30% of the patients have substantial disease progression while still awaiting LT, leading to removal from the waiting list [1][2][3]; in order to reduce progression, all patients are considered for local treatment whilst awaiting LT. Radiofrequency ablation (RFA) [4], percutaneous ethanol injection (PEI) and transcatheter arterial chemoembolization (TACE) [5] have become a standard of care for HCC as a bridge to LT despite the lack of a controlled trial confirming a survival advantage or of superiority of one treatment over another. Herein, we report our center's experience with the safety and efficacy of conformal radiotherapy (CRT) as another treatment option for bridging therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of crude survival rates, liver resection and transplant have the same results [5,6]. Nevertheless, disease-free survival is much better in patients undergoing liver transplant for a single, small HCC (less than 3 cm in diameter) [7]. Post-surgery recurrence of the disease is usually located in the liver, and occurs within two years of resection; sometimes it can appear as a metachronous lesion rather than a real recurrence of previous neoplasm [8].…”
Section: Liver Resection and Combined Non-surgical Treatmentsmentioning
confidence: 99%